The Role of Parenting Patterns in Developing Children's Leadership - Erlangga, Gaga; Arifin, Shokhibul; Asrori, Asrori (Al Ulya: Jurnal Pendidikan Islam, 2025)
This study aims to examine the influence of parenting patterns on leadership development in children. Leadership in children is an essential aspect in the development of individual children, which is influenced by various factors, one of which is parenting patterns. Baumrind, Maccoby & Martin's theory of parenting styles is used as an analytical framework. The research method used is qualitative with a case study approach. Data collection was carried out through in-depth interviews with children and parents. The study results showed that authoritative parenting patterns positively correlate with the development of prosocial leadership in children, characterized by the ability to make decisions, effective communication, cooperation, recreation, and innovation. Conversely, authoritarian and permissive parenting patterns tend to inhibit optimal leadership development. These findings support Baumrind's theory that authoritative parenting is the most effective parenting style in supporting children's social and emotional development. The implication of this study is that parents should apply consistent, warm parenting patterns and provide clear boundaries to support children's leadership development.